2021
DOI: 10.1002/adfm.202104641
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Optical Sensing of Strain and Humidity: A Patterned Dual‐Responsive Semi‐Interpenetrating Network of a Cholesteric Main‐Chain Polymer and a Poly(ampholyte)

Abstract: Main-chain cholesteric liquid crystal polymers are a promising candidate for the development of responsive photonic devices due to the combination of selective reflection and soft, elastic properties, but it is difficult to enhance these materials with new kinds of responsiveness due to the inherent lack of mesogenic side groups. Here, a new strategy is showed to obtain a dualresponsive elastic cholesteric polymer material by preparing a semi-interpenetrating network consisting of a cholesteric main-chain poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…At false(λmax,swollen/λmax,dryfalse)1=32%$({\lambda _{\max ,swollen}}/{\lambda _{\max ,dry}}) - 1 = 32\, the water uptake is comparable to photonic hydrogels based on tightly crosslinked ChLC networks [ 46 ] and slightly higher than other humidity‐sensitive ChLCE formulations. [ 35 ] The opposite process, deprotonation of a protonated film in deionized water, proceeds slowly. After 14 days, the peak reflected wavelength when swollen had slightly shortened to λ max ≈ 650 from 680 nm, and after another 28 days, to λ max ≈ 610 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At false(λmax,swollen/λmax,dryfalse)1=32%$({\lambda _{\max ,swollen}}/{\lambda _{\max ,dry}}) - 1 = 32\, the water uptake is comparable to photonic hydrogels based on tightly crosslinked ChLC networks [ 46 ] and slightly higher than other humidity‐sensitive ChLCE formulations. [ 35 ] The opposite process, deprotonation of a protonated film in deionized water, proceeds slowly. After 14 days, the peak reflected wavelength when swollen had slightly shortened to λ max ≈ 650 from 680 nm, and after another 28 days, to λ max ≈ 610 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The commonly used chiral dopant "Paliocolor LC 756," (3R,3aR,6S,6aR)-hexahydrofuro [3,2-b]furan-3,6-diyl bis(4-((4-(((4-(acryloyloxy)butoxy)carbonyl)oxy)benzoyl)oxy)benzoate), [30][31][32]34,35] is not employed in this chain extension reaction, as LC 756 contains carbonate groups [36] that have been shown to be labile during the thiol-acrylate Michael addition, thereby influencing the final ink. [23] Reactions between carbonates and primary amines have also been widely reported; using chiral dopant LC 756 in an amine-acrylate addition reaction procedure would likely lead to undesired side products.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the complexity of human physiological signals, it is often necessary to judge the health status of the human body through multiple information at the same time, which requires wearable sensor systems capable of numerous sensing functions [ 45 , 46 , 47 ]. Specifically, as shown in Figure 1 , the signals that the wearable sensor can monitor include movement [ 48 , 49 , 50 ], pressure [ 51 , 52 , 53 ], temperature [ 54 , 55 , 56 ], humidity [ 57 , 58 , 59 ], and heart rate [ 60 , 61 , 62 ]. In addition, through the electrochemical analysis of human secretions (such as sweat [ 63 ] and tears [ 64 ]), a variety of physiological signals can be obtained [ 65 ], such as the concentration of glucose [ 66 , 67 ], lactic acid [ 68 , 69 ], sodium, and potassium ions [ 70 , 71 , 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…Constructing the semi-interpenetrating polymer network (it usually consists of the cross-linked polymer network interpenetrated by another linear polymer without the cross-linker) can integrate special properties of distinct polymer chains, and is therefore considered as a straightforward strategy for merging and adjusting the functions of polymeric hydrogel electrolytes. [16][17][18] For example, Zhi et al demonstrated that the sulfobetaine/cellulose hydrogel electrolyte possessing a semi-interpenetrating network structure could deliver an ultra-high ionic conductivity of 24.6 mS cm −1 with a high stretchability of 920%. [11] The as-developed Zn-MnO 2 battery with this polyzwitterionic hydrogel electrolyte gained the ultra-fast rate performance and long-term stability of 10 000 cycles at an ultra-high current density of 30 C. Wang and co-workers reported a flexible gel polymer electrolyte of PAM-PVP-H 3 PO 4 with a semi-interpenetrating network structure, with which the fabricated supercapacitor demonstrated a high capacitance retention under bending, stretching, and low temperature.…”
mentioning
confidence: 99%